Powrót do przedkryzysowej polityki pieniężnej a stabilność systemu finansowego - Skibińska-Fabrowska, Ilona (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
Faced with the financial crisis in 2008, the central banks used conventional monetary policy instruments. However, the problem of zero lower bond forced them to use unconventional monetary policy instruments - quantitative easing carried out as part of the so-called central bank balance sheet politics and relying on the buying by the central bank of di&erent kinds of financial assets - resulting in stabilization of the situation on financial markets in conditions of low long-term interest rates. Balance sheet totals of the central banks rose repeatedly. Their structure also changed. At present possible effects for the stability of the financial system of the return to the pre-crisis monetary policy are the topic of debate. The exit strategy is giving rise to a significant risks and the coordination of economic policy and the transparency of action taken by monetary authorities can only minimize possible negative effects